Fundamentalisme Agama: Antara Fenomena Dakwah dan Kekerasan Atas Nama Agama - Dahlan, Fahrurrozi (Jurnal Ilmu Dakwah, 2012)
Fundamental Islam is a religious view that has its roots in orthodox understanding who interpret the religious texts in rigid, static and exclusive ways. Fundamentalism involves efforts to purify or reform the beliefs and practices of the followers according to their principles. The study of fundamentalism is a part in diversity in understanding a religion which has its own characteristics, not least reflected in their interpretation of the doctrine of rigid and literalist religion. This is motivated by several factors including; interpretation as it is important for them to maintain the purity of doctrine and practice. Next characteristic that the application of the doctrine as a whole is the only way to save mankind from ignorance. The conclusion of this study is the rise of fundamentalism in Islam, is actually a strong reaction on the growth of Islamic liberalism.